Optimizing YouTube for Interactive Arabic Learning in Pesantren: Effective Content Creation Strategies - Arisandi, Yusuf; Habib, Moh. Tohiri (Postgraduate of IAIN Metro Lampung Indonesia, 2025)
In the evolving landscape of Arabic language education, YouTube has emerged as a powerful medium for enhancing listening and speaking skills in Islamic boarding schools, where traditional oral-based instruction predominates. This study aims to explore strategies for optimizing YouTube as an interactive learning tool tailored to the pedagogical and cultural context of pesantren. Using a qualitative case study at Pesantren Darullughah Wadda’wah in East Java, Indonesia, data were collected through semi-structured interviews with 22 participants (10 teachers and 12 students), focus group discussions involving 18 students across three groups, and classroom observations in selected Arabic classes, representing 40 participants with basic to intermediate Arabic proficiency. The findings reveal that structured exposure to Arabic-language YouTube content, combined with visual cues, interactive exercises, and contextual learning, significantly improves comprehension and speaking fluency. However, challenges such as inconsistent content quality, digital distractions, and limited technological access hinder optimal use. The novelty of this research lies in its proposed hybrid learning model, integrating YouTube-based materials with traditional teaching methods to preserve the strengths of oral transmission while embracing digital innovation. This study offers practical recommendations for educators and content creators in designing effective, culturally relevant digital resources for Arabic language learning in pesantren.